Skepticism, relativism, and religious knowledge a Kierkegaardian perspective informed by Wittgenstein's philosophy - Harvey, Michael G. (Pickwick, 2013)
Skepticism, Relativism, and Religious Knowledge shows where responses to skepticism and relativism by Karl Barth and Reformed epistemology have led to impasses, and reconstructs their insights in a more robust response that does not depend on making excessive claims about our epistemic capacities. This response is based on a more nuanced conception of the relationship between trust, doubt, faith, and reason, and a Kierkegaardian perspective on religious knowledge that stresses the role of the will and the intellectual and theological virtues